PERANAN PERSON IN CHARGE DALAM PENYELENGGARAAN MICE DI BICC THE WESTIN RESORT - AA. Sagung Amega Indra Theresa; I Wayan Suardana; I GPB. Sasrawan Mananda (Jurnal IPTA (Industri Perjalanan Wisata), 2015)
Nowadays Bali has developed into a MICE tourist destination. Several events hav been a successfuly held in Bali. The event such of the ASEAN Summit and Climate Change Summit 2012, ASEAN Summit and the ASEAN Foreign Ministers Meeting. Behind the success of the international MICE events in Bali, there are the role of person who are competent to make it happen. Human resources in the area of MICE services have a very important role for MICE events took place. They are the one who hold the key to the success of the event. One of them is a representative of the hotel (venue) where the convention was held as a person in charge who will be contacted by the organizers to communicate all necessary purposes. The person in charge holds the key to the success of the hotel (venue) in providing the best service to convention delegates, and play crucial part of convincing the organizers to use hotel as a venue. This study was conducted to determine how the specification of the role of the person in charge in the organization of international MICE event.